How to Create and Maintain a Social Problem: Critically Deconstructing the Canadian National Drug Strategies 1987-2014 - Dastouri, Serenna (Université d'Ottawa / University of Ottawa, 2015)
This thesis explores the evolution of the discourses that constitute the social problem of drug use in Canada as described throughout the three Canadian drug strategies: the National Drug Strategy 1987-1992, the Canadian Drug Strategy 1992-2007 and the National Anti-Drug Strategy 2007-2014. In order to do so the author engages with Foucaudian concepts of discourse, power and knowledge to conduct an archaeological analysis of government texts produced during each time period. In particular, the author places a focus on how drug use, drug users, the impact of drug use on Canadian society and the perceived necessary responses to the drug problem are constructed through various discourses. The findings help the author propose a framework to examine how social problems may be politicized in general. The framework highlights the tendency for social problems to emphasize appropriate social norms, be selective in their incorporation of evidence, marginalize those who are considered problematic and politicize objects in a vague manner.
Keywords: Drug; Canada